Since the question is 3(2a), then just write it out. 3(2a) is 2a+2a+2a or 6a.
(6ab + 9b)/(2a + 3) = 3b(2a + 3)/(2a + 3) = 3b
2a-3+4b-2a-b-3+5=3b-1
9a +8 -2a -3 -5a = 2a +5
(6a3 - 19a2 + 15a)/(2a - 3) = a(6a2 - 19a + 15)/(2a - 3) = a(2a - 3)(3a -5)/(2a -3) = a(3a - 5)
It is the expression 3 + 2a.
9a +8 -2a -3 -5a = 2a +5
(a - 6)(2a + 3)
To simplify the expression 2a - 3 + 4b - 2a - b - 3 + 5, we first combine like terms. Combining the terms with 'a', we have 2a - 2a = 0. Combining the terms with 'b', we have 4b - b = 3b. Combining the constants, we have -3 - 3 + 5 = -1. Therefore, the simplified expression is 3b - 1.
5a- 2a = 3
9a +8 -2a -3 -5a = 2a +5
Start with simplifying: 2a + -3 = 5 and reordering: -3 + 2a = 5. Then add '3' to each side of the equation: -3 + 3 + 2a = 5 + 3 and you get 2a = 8 once all like terms are combined. The last step is to divide both sides by 2 and you get the answer, which is a = 4.